Studies in law, politics, and society. Vol. 61 - Sarat, Austin (Studies in law, politics, and society., 2013)
This volume of Studies in law, politics and society brings together an international spread of legal scholars, presenting a varied collection of chapters. Chapters include: child abduction during the military dictatorship in Argentina; a novel approach to empirical research on legal framing from the University of California, Berkeley; the role of silence in law and film from Israel; a chapter from Sweden on the use of video in the court of appeal; and finally two chapters on the supreme court in the USA, one looking at influences through social capital on supreme court decision makers and the second looking at the self-perception and public perception of the supreme court.